Avaliação da permeação e do efeito protetor UV de produtos capilares por Espectroscopia Raman Confocal - (:unkn) unknown (Universidade Brasil, 2022)
The hair fiber suffers a lot of structural changes due to the chemical products exposition and the solar radiation, being the ultraviolet radiation (UV) the principal. The goal of this thesis is analyzed the photo protection and maintenance of the aminoacids concentrations in the hair fibers after the A and B compound suffer UV radiation, using the Raman Confocal electroscopy to measure. The Raman Confocal electroscopy inquires the biochemical and structural alterations of the fiber before and after the solar radiation exposition. In the project, the Raman River Diagnostics system was used the laser with 785 nm excitation and 21 mW of potency. The Raman range measured was between 400 - 1800 cm-1, besides that, the hair fiber was setted up in a 40x objective lens under a quartz window. 15 hair fibers for sample group were analyzed and 21 spectrums per fiber was collected, containing spectrum in the 1575 cm-1 zone. The homogeneity analysis of the virgin hair sample allowed the permeance evaluation in the samples irradiated and no irradiated with UV radiation. In the end, the compound A was more efficiency than the compound B. The efficiency variance of the samples due to the irradiation or the intrinsic features was possible to analysis too. The conclusion of the compound A and compound B analysis was necessary to describe the spectral alterations because of the UV radiation damages and the Raman Confocal electroscopy contributes in the comparation of the products A and products B efficiency.
Keywords: Radiação ultravioleta; Permeação de ativo; Espectroscopia Raman; Fibra capilar; Engenharia Biomédica (Bioengenharia)